Kara pozbawienia wolności w perspektywie ewolucji systemów penitencjarnych oraz zmian w zakresie koncepcji penologicznych - Kalisz, Tomasz (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2020)
For a long time, practically until the 19th century, with few exceptions from earlier centuries, the prison was associated rather with dungeons, basements, towers and towers, as a place of torture, holding perpetrators for pronouncing a sentence or executing the death penalty, or other punishments. The imprisonment was more preventive than repressive, even if the prisoner happened to spend the rest of his life in this way. In order to bring prison sentences to the light of day and place them in the first place of the means of response to crime, a fundamental change in the concept of punishment was needed. As long as it was a socialized form of anger and only that, there could be no question of the unique role of prison. Only when the punishment losing more and more the features of brutal retaliation and retaining to some extent the pursuit of deterrence, takes on the elements of correctional sanction, a new era begins in the history of prison. This slow evolution from retaliatory to corrective sanction has shifted the focus from death penalty and corporal punishment to imprisonment. The study presents the evolution of prison from individual homes of improvement towards ordered penitentiary systems.
Keywords: imprisonment; convicted; penitentiary system; criminal punishment